EFL Pre-Service Teachers' Perceptions of their Experience in Using Short Stories in a Bichronous E-learning Environment - Pardede, Parlindungan; Purnamasari, Asri (JET (Journal of English Teaching), 2025)
Short stories and e-learning are two effective tools for EFL learning and teaching due to their potential to promote language, communication, cultural understanding, and thinking skills and to facilitate enjoyable, interesting, and encouraging learning. Yet, studies exploring students' experience in using literature and EFL e-learning environments are still meager. This study aimed at exploring the perceptions of eight EFL pre-service teachers at Universitas Kristen Indonesia. Jakarta of their experience in using short stories in an EFL e-learning environment. To elucidate their voices of their experiences, data collected employing FGDs and semi-structured interviews was analyzed using the content analysis technique. The results revealed that the majority of the participants had a positive perception of using short stories to learn English in a bichronous (combination of synchronous and asynchronous) e-learning environment. They viewed that short stories use through a bichronous e-learning platform in the course effectively developed their language skills, honed their research skills, made learning convenient and interesting, and broadened their knowledge and cultural understanding. Many of them were even encouraged to keep on reading online short stories for pleasure. Thus, short stories can be an effective tool for enhancing the performance of EFL learners studying through bichronous e-learning.